2013
DOI: 10.1007/s40292-013-0002-7
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Cognitive Function, Depressive Behaviour and Sleep Quality with 24-h Urinary Sodium Excretion in Patients with Essential Hypertension

Abstract: The current study demonstrated that better cognitive function, but not depressive behaviour and sleep disturbance, is related to decreased sodium intake as evaluated by 24-h urinary sodium excretion. Studies are needed to highlight the mechanisms regarding the relationship between cognitive function and sodium intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 21 publications
1
38
1
Order By: Relevance
“…Contrary to our hypothesis, and to results of some prior studies (5, 6, 19), we did not find that higher sodium intake was associated with poorer cognitive performance. Instead, we found that lower dietary sodium was associated with poorer performance on tests of global (MMSE) and executive (Trails B) cognitive function independent of lifestyle, comorbidities medication use and kidney function.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to our hypothesis, and to results of some prior studies (5, 6, 19), we did not find that higher sodium intake was associated with poorer cognitive performance. Instead, we found that lower dietary sodium was associated with poorer performance on tests of global (MMSE) and executive (Trails B) cognitive function independent of lifestyle, comorbidities medication use and kidney function.…”
Section: Discussioncontrasting
confidence: 99%
“…Direct comparison of the studies is hampered by methodological differences, and differences in study samples. The study by Afsar (19) examined urine sodium excretion levels in a younger sample of adults in Turkey, recently diagnosed with essential hypertension. Results showed that lower urine sodium excretion levels were associated with higher MMSE scores (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that high-salt diet, which is a common environmental factor in western countries as well as in more and more developing countries, is associated with cognitive decline [3,4,5]. Moreover, high-salt diet impairs cognitive function in mouse models [6].…”
Section: Discussionmentioning
confidence: 99%
“…Several independent epidemiological investigations have shown that high-salt diet is associated with cognitive decline in human [3,4,5]. Recently, it’s found that high-salt diet could impair cognitive function in wild-type mice [6].…”
Section: Introductionmentioning
confidence: 99%